2012
DOI: 10.1038/clpt.2012.171
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Assessment of the Drug Interaction Between Levothyroxine and Warfarin

Abstract: Most drug interaction resources suggest that levothyroxine can dramatically potentiate the effect of warfarin. However, the mechanistic basis of the interaction is speculative, and little evidence supports a meaningful drug interaction. We conducted a population-based nested case-control study to examine the risk of hospitalization for hemorrhage following the initiation of levothyroxine in a cohort of 260,076 older patients receiving warfarin. In this group, we identified 10,532 case subjects hospitalized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…In addition, none of these studies specifically investigated the effect of potential DDIs on variations of TSH levels, levothyroxine prescriptions and dosage. Pincus et al [23] evaluated the effect of warfarin-levothyroxine interactions on the risk of hospitalisation but did not investigate changes in TSH levels on the trend of levothyroxine prescriptions and/or doses when these drugs were prescribed concurrently. On the other hand, Taylor et al [24] investigated the pattern of levothyroxine use as a function of TSH levels in a UK general population but did not consider the effect of potential DDIs on levothyroxine prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, none of these studies specifically investigated the effect of potential DDIs on variations of TSH levels, levothyroxine prescriptions and dosage. Pincus et al [23] evaluated the effect of warfarin-levothyroxine interactions on the risk of hospitalisation but did not investigate changes in TSH levels on the trend of levothyroxine prescriptions and/or doses when these drugs were prescribed concurrently. On the other hand, Taylor et al [24] investigated the pattern of levothyroxine use as a function of TSH levels in a UK general population but did not consider the effect of potential DDIs on levothyroxine prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports suggest that concomitant use of warfarin and levothyroxine can result in hospitalization and a need for significant warfarin dosage adjustments to restabilize the INR response . However, a large population‐based, case–control study evaluating the impact of the the warfarin–levothyroxine interaction found no relationship in warfarin‐receiving patients between the initiation of levothyroxine and hospitalization for bleeding, and concluded that this interaction was not clinically significant .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the frequency of INR monitoring and reducing the dose of warfarin as needed to prevent excessive anticoagulation following levothyroxine initiation has been suggested as a reasonable clinical management option . It is possible that failure to consider the influence of INR monitoring and warfarin dose adjustments may have led the authors of the aforementioned case–control study to erroneously conclude that there no warfarin–levothyroxine interaction, and thus explain the lack of an association between levothyroxine initiation and bleeding .…”
Section: Introductionmentioning
confidence: 99%
“…36 We also considered antiplatelet and anticoagulant prescriptions dispensed to patients within 1 year before surgery for those with Ontario Drug Benefit coverage (i.e., all those > 65 years of age). 37 Each fracture and procedure type were recorded.…”
Section: Outcome Measurementioning
confidence: 99%